Use of Preexpanded Forehead and Neck Skin in Case of Giant Facial Hairy Naevus: Planning and Technique - Sharma, Mukesh Kumar; Kumar, Naveen; Babu, V. Suman; Tiwari, Vinay Kumar (Indian Journal of Plastic Surgery, 2020)
A congenital nevi is a pigmented patch which requires complete surgical excision for cosmetic reasons. Here, we report a case of a patient with facial hairy pigmented lesion, occupying the right half of her face since birth, who underwent complete surgical excision and staged reconstruction utilizing, preexpanded forehead and neck skin. We used two rectangular tissue expanders with 150 and 300 cubic cm of volumes inserted in the forehead and the neck, respectively. The length of the expanders selected were equal to 1.2 to 1.5 times the length of their respective lesions, whereas the width of the base of the expanders were approximately similar to the width of their defects. It is concluded with this case report that tissue expansion provides a good cosmetic and anatomical correction to cover large defects, with adjacent skin having similar properties.
Keywords: congenital; nevi; expander